Geophysical case study of the Woodlawn orebody, New South Wales, Australia : the first publication of methods and techniques tested over a base metal orebody of the type which yields the highest rate of return on mining investment with modest capital requirements - Whiteley, Robert J. (Pergamon Press, 1981)
The Woodlawn orebody is located in eastern New South Wales, Australia. It is one of an important class of massive, copper-lead-zinc, stratiform volcanogenic mineral deposits and has reserves of about 10 million tonnes of ore. Deposits such as Woodlawn are the object of considerable worldwide exploitation effort because they yield the highest rate of return on mining investment with modest capital requirements. This detailed geophysical case study contains individual contributions by professionals from diverse backgrounds (industry, government and university) and includes the latest geophysical methods. It is the only detailed geophysical study of an economic sulphide deposit ever undertaken for educational purposes.